TRUST AS A MEDIATOR OF DONOR LOYALTY IN ISLAMIC DIGITAL PHILANTHROPY: THE ROLES OF EASE AND ENJOYMENT - Cantika A'malina Annisa; Herni Justiana Astuti (UIN Sunan Gunung Djati Bandung, 2026)
The development of digital based Islamic philanthropy has transformed the way people participate in charitable activities, making it essential to understand the factors that encourage donors to remain loyal to a donation platform. Research that specifically examines donor loyalty by integrating perceived ease of use, perceived enjoyment, and trust within the Technology Acceptance Model (TAM) framework remains limited, particularly in the context of Islamic digital philanthropy. This study aims to analyze how perceived ease of use and perceived enjoyment influence donor loyalty, both directly and indirectly through trust, on the Sobat Berbagi Lazismu Banyumas platform. This research employed a quantitative approach by collecting data from 124 users of the platform through a purposive sampling technique. The data were processed using Partial Least Squares–Structural Equation Modeling (PLS-SEM) with SmartPLS 3 software. The results indicate that both perceived ease of use and perceived enjoyment positively contribute to building donor trust and strengthening donor loyalty. Trust was also found to have a significant positive impact on donor loyalty. Furthermore, trust successfully mediates the relationship between perceived enjoyment and donor loyalty, whereas its mediating role between perceived ease of use and donor loyalty is not statistically supported. These findings suggest that creating an enjoyable donation experience plays a more important role in fostering long-term donor commitment than merely providing a user-friendly system.